Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
Keywords: _r:AddedByZotZen

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen